The Brussels zoo: A mirror of 19th century modes of thought on the city, science and entertainment - Wim Lambrechts (Brussels Studies, 2014)
In the 19th century, four zoological gardens were created in Belgium. The first was founded in Antwerp in 1843, followed by Ghent, Brussels (both in 1851) and Liège (1865). The Brussels zoo was conceived as a “salon public”, a public parlour offering nice walks, enlivened with an animal collection to ward off boredom and stimulate scientific interest. This article, more than a factual history based on archives, attempts to place the zoo in the spirit of the age and the modes of thought of the 19th century. The zoo profiled itself as a scientific institution in the city, engaging in (theoretical) classification and (practical) acclimatization. Its cultural activities, perhaps even more than its animals, made it a popular attraction for the middle classes.